Psychologically Alienated Characters: An Analytical Narrative Approach in The Novels of Suheil Sami Nader/ الشخصيات المستلبة نفسيًا: مقاربة سردية تحليلية في روايات سهيل سامي نادر - Nagham Noori Awwad; Lateef Mahmoud Mohammed (Ijaz Arabi Journal of Arabic Learning, 2026)
This research examines the psychologically alienated characters in the novels of Suheil Sami Nader, focusing on the narrative and psychological elements that distinguish these characters. Psychological alienation is defined as a state of dissociation between the self and reality, where characters suffer from a loss of identity and an inability to interact healthily with their environment. The findings illustrate that Nader employs innovative narrative techniques such as interior monologue and manipulation of time to enhance the sense of estrangement experienced by alienated individuals. By analyzing multiple characters, the research demonstrates how internal and external conflicts influence the behavior and decisions of individuals, causing them to become trapped in closed loops of psychological disturbance. This research seeks to achieve several objectives, such as understanding the nature of psychologically alienated characters in Suheil Sami Nader's novels and how social and cultural circumstances influence the formation of these characters. Another objective is to shed light on the narrative methods Nader uses to depict the psychological challenges faced by individuals, and to show how these characters interact with the vibrancy of life and its suffering in various contexts. The research also aims to provide a critical approach to the genre of literature that deals with psychological alienation, analyzing its impact on the reader and its role in spreading awareness about psychological and social issues.